2017
DOI: 10.1007/s00167-017-4494-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral knee biomechanics

Abstract: This article reviews the evidence for the roles of the anterolateral soft-tissue structures in rotatory stability of the knee, including their structural properties, isometry, and contributions to resisting tibial internal rotation. These data then lead to a biomechanical demonstration that the ilio-tibial band is the most important structure for the restraint of anterolateral rotatory instability. Level of evidence V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 68 publications
4
33
0
1
Order By: Relevance
“…In addition, Monaco et al [ 21 ], utilizing a navigation system, demonstrated the clinical impact of anterolateral reconstruction in the context of ACL repair and demonstrated that this reduced ALRI [ 21 ]. Recently, a further study showed that while the CITB does provide some resistance, the femoral attachments of the distal ITB may be stronger and better aligned to provide this action [ 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Monaco et al [ 21 ], utilizing a navigation system, demonstrated the clinical impact of anterolateral reconstruction in the context of ACL repair and demonstrated that this reduced ALRI [ 21 ]. Recently, a further study showed that while the CITB does provide some resistance, the femoral attachments of the distal ITB may be stronger and better aligned to provide this action [ 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since these anterolateral structures are injured during a pivot-shift phenomenon and have been shown to be biomechanically important in resisting pivot shift, it has been suggested that reconstructing some aspect of these structures as an adjunct to intra-articular ACL reconstruction may reduce the incidence of post-operative pivot-shift ALRI [ 9 , 14 , 23 , 24 , 31 ]. As a result, lateral extra-articular procedures concomitant with intra-articular ACL reconstruction have become increasingly popular.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral plateau is convex, compared to the concave medial plateau with increased congruity with its femoral condyle, which leads to more translational motion at the lateral side of the knee. 7,8 The posterior slope of the knee also contributes to the magnitude of the pivot shift, as the femoral condyle can translate more with an increased posterior tibial slope. 9 Increased motion at the anterior lateral tibial plateau may be responsible for tibial subluxation at the initiation of knee flexion 10 and may be associated with the severity of the pivot shift.…”
Section: Tibial Bone Morphologymentioning
confidence: 99%
“…Damage to these anterolateral soft tissue structures have been shown to elicit a positive pivot shift phenomenon-a finding classically indicative of ACL tear (Hughston et al 1976;Bull et al 1999)-suggesting this tissue is involved in maintaining similar axes of knee stability as the ACL. Moreover, anterolateral structures have been suggest to have a more important role in resisting internal rotation because of the larger moment arm they carry compared to the more centrally located ACL (Amis 2017).…”
Section: The Segond Fracturementioning
confidence: 99%